Effect of fat mass and lean mass on bone mineral density in postmenopausal and perimenopausal Thai women - Namwongprom S. (2014)
Background: The purpose of this study was to investigate the association between fat mass, lean mass, and bone mineral density (BMD) in postmenopausal and perimenopausal Thai women. Methods: A cross-sectional study was conducted in 1579 healthy Thai women aged 40-90 years. Total body, lumbar spine, total femur, and femoral neck BMD and body composition were measured by dual x-ray absorptiometry. To evaluate the associations between fat mass and lean mass and various measures of BMD, multivariable linear regression models were used to estimate the regression coefficients for fat mass and lean mass, first in separate equations and then with both fat mass and lean mass in the same equation. Results: Among the study population, 1448 subjects (91.7%) were postmenopausal and 131 (8.3%) were perimenopausal. In postmenopausal women, after controlling for age, height, and duration of menopause, both fat mass and lean mass were positively correlated with BMD when they were analyzed independently of each other. When included in the same equation, both fat mass and lean mass continued to show a positive effect, but lean mass had a signifcantly greater impact on BMD than fat mass at all regions except for total body. Lean mass but not fat mass had a positive effect on BMD at all skeletal sites except the lumbar spine, after controlling for age and height in perimenopausal women. Conclusion: Lean mass had a signifcant beneficial effect on BMD in both postmenopausal and perimenopausal women and can be considered as one of the determinants of bone mass. The effect of the fat mass was related to menopausal status, but only demonstrated a positive impact in perimenopausal women. © 2013 Namwongprom et al publisher and licensee Dove Medical Press Ltd.